Sometimes you ride the Pegasus, sometimes you take the road: Mitchell on laws in biology - Plutynski, Anya (THEORIA. An International Journal for Theory, History and Foundations of Science, 2023)
Mitchell’s philosophical contributions are part of an ongoing conversation among philosophers and scientists about laws and unification in biology, going back at least to Darwin. This article situates Mitchell in this conversation, explains why and how she has correctly guided us away from false idols, and engages several difficult questions she leaves open. I argue that there are different epistemic roles laws (or models describing lawlike regularities) play in biological inquiry. First, they play the role of “how possibly” explanations, akin to Herschel’s characterization of Whewell’s “a priori Pegasus,” and second, they provide descriptions of empirical regularities, akin to the “plain matter of fact roadster.”